Fredholm and Volterra nonlinear possibilistic integral equations - GAL, Sorin G.; IANCU, Ionuț T. (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
In this paper we study the nonlinear functional equations obtained from the classical integral equations of Fredholm and of Volterra of second kind, by replacing there the linear Lebesgue integral with the nonlinear possibilistic integral. Mathematics Subject Classification (2010): 45B05, 47H10, 28E10, 28A99.